Spatial Effects of Cocoa Production on Rural Economy in Idanre-Ifedore Area, Ondo State of Nigeria - Adefila , J. O (Asian Journal of Agriculture and Rural Development, 2013)
Agriculture has been the main-stay of Nigeria’s economy of which cocoa production plays a significant role in the acceleration of the national gross domestic product (GDP), in terms of employment generation, feeding the local industries with raw materials and sustains the rural livelihood until about the mid-1970s that witnessed oil boom resulting in the neglect of the sector coupled with the introduction of structural adjustment programme (SAP) in 1986 that killed the morale of cocoa producers. The cardinal objective of the study was to examine the effects of cocoa industry on the rural livelihoods in Idanre-Ifedore area, Ondo State of Nigeria. Primary data were generated from 80 randomly sampled households in the study area. Also, a focus group discussion was conducted among the communities that were involved in cocoa production. Secondary data were collected from the ministry of agriculture and rural development, cocoa development units, cocoa research institute of Nigeria (CRIN), official gazettes, federal office of statistics and documented materials. The study employed descriptive statistics namely mean, averages and percentages to summarize the data. Also, inferential statistics such as analysis of variance (ANOVA) and regression statistics were employed to analyse the data. It revealed F-test value of 3.85 and a critical value of 2.53 indicates a significant variation in cocoa output at 0.05 probability level among the farmers in the study area. The study examined the relationship between cocoa output and socio-economic traits of the farmers. The regression result showed that age of cocoa farmers (r = .825), annual income (r = .631), age of cocoa farms (r = .755) and cocoa farm size (r = .648) have strong positive correlation coefficients while family size (r = .385) and cocoa farming experience (r = .413) were found to be positive but weak correlation at 0.05 alpha value. On the basis of the findings, one recommends among other things a mass enlightenment campaign at community levels through cocoa research institutes and field extension workers persuading farmers to be planting hybrid disease-resistant cocoa trees to replace the moribund trees. Moreover, government should increase producer price in order to encourage the potential cocoa farmers to put in their best and subsidize the agro-chemicals thereby making it affordable for peasant farmers. By doing so, the country can still assume her rightful position as one of the leading countries as exporter of cocoa in the world.